2019
DOI: 10.1101/764183
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HELLS and PRDM9 form a Pioneer Complex to Open Chromatin at Meiotic Recombination Hotspots

Abstract: Chromatin barriers prevent spurious interactions between regulatory elements and DNAbinding proteins. One such barrier, whose mechanism for overcoming is poorly understood, is access to recombination hotspots during meiosis. Here we show that the chromatin remodeler HELLS and DNA-binding protein PRDM9 function together to open chromatin at hotspots and provide access for the DNA double-strand break (DSB) machinery. Recombination hotspots are decorated by a unique combination of histone modifications, not found… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 99 publications
0
1
1
Order By: Relevance
“…Although it has been suggested that ZCWPW1 might recruit the DSB machinery (M. Spruce et al, 2019), our data imply DSB formation and positioning are largely unaffected by loss of ZCWPW1 and occur at PRDM9bound hotspots. Moreover DMC1, RAD51 and RPA2 loading also appear normal (Figure 7A and (M. Li et al, 2019)), but asynapsis and failure to remove DMC1 imply a profound downstream impact.…”
Section: Discussioncontrasting
confidence: 64%
“…Although it has been suggested that ZCWPW1 might recruit the DSB machinery (M. Spruce et al, 2019), our data imply DSB formation and positioning are largely unaffected by loss of ZCWPW1 and occur at PRDM9bound hotspots. Moreover DMC1, RAD51 and RPA2 loading also appear normal (Figure 7A and (M. Li et al, 2019)), but asynapsis and failure to remove DMC1 imply a profound downstream impact.…”
Section: Discussioncontrasting
confidence: 64%
“…Indeed, DNA methylation in insects is largely associated with gene bodies and not with heterochromatic transposable elements (72)(73)(74)(75), apparently contradicting the suggested specialized role of CDCA7-HELLS in maintaining DNA methylation at heterochromatin. It will be important to test the functional significance of CDCA7-hemimethylated CpG binding in other processes where HELLS and/or CDCA7 play roles, such as DNA repair, resolution of DNA-RNA hybrids, and macroH2A deposition (49,62,(76)(77)(78)(79)(80)(81)(82). Third, the low resolution of our current cryo-EM structure of the CDCA7-nucleosome complex prevented us from dissecting the structural basis for hemimethylated CpG recognition by CDCA7 at atomic resolution.…”
Section: Discussionmentioning
confidence: 99%